2013
DOI: 10.1371/journal.pone.0065020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Factor of Activated T-Cells (NFAT) Suppresses Accelerated Atherosclerosis in Diabetic Mice

Abstract: Objective of the StudyDiabetic patients have a much more widespread and aggressive form of atherosclerosis and therefore, higher risk for myocardial infarction, peripheral vascular disease and stroke, but the molecular mechanisms leading to accelerated damage are still unclear. Recently, we showed that hyperglycemia activates the transcription factor NFAT in the arterial wall, inducing the expression of the pro-atherosclerotic protein osteopontin. Here we investigate whether NFAT activation may be a link betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
4
35
1
1
Order By: Relevance
“…Considering that NFAT activity is regulated by calcineurin (45), our findings might help explain these inhibitory effects of calcineurin inhibitors on endotoxemia and pulmonary injury. Collectively, our data suggest a pathological role for the calcium/ calcineurin-NFAT signaling axis in the development of septic lung damage similar to that proposed for the development of cardiac hypertrophy (22), diabetes-induced vascular inflammation (46), atherosclerosis (39,47), and acute pancreatitis (24). HMGB1 and IL-6 are potent proinflammatory cytokines and markers of systemic inflammation in endotoxemia and sepsis (48,49).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Considering that NFAT activity is regulated by calcineurin (45), our findings might help explain these inhibitory effects of calcineurin inhibitors on endotoxemia and pulmonary injury. Collectively, our data suggest a pathological role for the calcium/ calcineurin-NFAT signaling axis in the development of septic lung damage similar to that proposed for the development of cardiac hypertrophy (22), diabetes-induced vascular inflammation (46), atherosclerosis (39,47), and acute pancreatitis (24). HMGB1 and IL-6 are potent proinflammatory cytokines and markers of systemic inflammation in endotoxemia and sepsis (48,49).…”
Section: Discussionsupporting
confidence: 68%
“…NFAT activity is generally considered to control aspects of tissue development during embryogenesis, including vasculogenesis, axonal outgrowth, muscle and bone formation, as well as maturation of the immune system (34)(35)(36)(37)(38). However, a growing body of literature also implicates NFAT signaling in inflammatory processes, such as atherosclerosis (39), autoimmune diseases (40), and acute pancreatitis (24). Here, we show that in vivo administration of the NFAT inhibitor (A-285222) readily blocked sepsis-induced NFAT-dependent tran- scriptional activity not only in the lung but also in the spleen, liver, and aorta, suggesting not only that NFAT is activated in sepsis but also that A-285222 is an effective inhibitor of NFAT.…”
Section: Discussionmentioning
confidence: 99%
“…This study succeeded earlier work which demonstrated that microRNA miR-204 down-regulation with subsequent up-regulation of anti-apoptotic and pro-proliferative transcription factors, nuclear factor of activated T Cells (NFAT) and hypoxia-inducible factor 1α (HIF-1α), correlated closely with PAH severity (122). Indeed, NFAT signaling has been implicated in adverse vascular remodeling post injury and atherosclerotic progression in diabetic mice (123,124). HIF-1α, on the other hand, is activated by a hypoxic ROS environment and has been shown to induce expression of vascular endothelial growth factor, thereby promoting VSMC proliferation (125) and subsequent atherosclerosis (126).…”
Section: Dna Repair and Effects On Atherosclerosissupporting
confidence: 77%
“…In agreement with our results, previous reports have demonstrated that osteopontin is induced by hyperglycemia in smooth muscle cells. Several mechanisms have been proposed, including activation of the PKC/Rho-kinase pathway (62) and activation of the transcription factor NFATc3 (63,64). Thus, hyperglycemia in diabetic patients may result in simultaneous activation of the contractile and synthetic gene programs, leading to increased risk of neointimal hyperplasia as well as hypertension and vasospasm.…”
Section: No Diabetesmentioning
confidence: 99%